Upper-Body Muscular Endurance Training Improves Performance Following 50 min of Double Poling in Well-Trained Cross-Country Skiers - Børve, Jørgen; Jevne, Steffen N.; Rud, Bjarne; Losnegard, Thomas (Frontiers in Physiology, 2017)
This study investigated the effect of muscular endurance training on O2-cost and performance in double poling (DP) on a rollerski treadmill. Twenty-two well-trained cross-country skiers (31 ± 4 years, 77 ± 9 kg, 181 ± 8 cm, VO2max running: 64 ± 5 mL·kg-1·min-1) were counter-balanced to either a combined muscular endurance and running interval training group (MET; n =11 (♂ = 9, ♀ = 2)), or an endurance running interval training group (ET; n =11 (♂ =9, ♀ = 2)). Both groups continued their normal low- and moderate intensity training, but replaced two weekly high intensity-training sessions with two project-specific sessions for 6 weeks. In these sessions, MET combined upper-body muscular endurance training (4x30 repetitions, 90 s rest between sets) and running intervals (3x4 or 2x6 min, 3 min rest), while ET performed running intervals only (6x4 or 4x6 min, 3 min rest). The DP test-protocol consisted of 50 min submaximal poling for O2-cost measurement, followed by a self-paced 1000-m performance test. In addition, subjects performed a VO2max test in running. MET increased muscular endurance (P<0.05) and 1RM in simulated DP (P<0.01) more than ET. Further, MET reduced the 1000-m time and O2-cost compared to baseline values (P<0.05), and tended to improve the 1000-m time more than ET (P=0.06). There were no changes in VO2max running or VO2peak DP in either MET or ET. In conclusion, 6 weeks of muscular endurance training increased both muscular endurance and 1RM in simulated DP. Further, specific upper-body muscular endurance training improved DP performance and thus, seems as a promising training model to optimize performance in well-trained cross-country skiers.